Shepherding a child's heart - Tripp, Tedd. (Wapwallopen, Pa. : Shepherd Press, 2005)
Shepherding a Child's Heart is about how to speak to the heart of your child. The things your child does and says flow from the heart. Luke 6:45 puts it this way: "out of the overflow of the heart the mouth speaks (NIV)." Written for parents with children of any age, this insightful book provides perspectives and procedures for shepherding your child's heart into the paths of life. - Back cover.
Preface to second edition -- Preface to first edition -- Foreword -- Introduction -- Part 1 : Foundations for biblical childrearing. Getting to the heart of behavior -- Your child's development : shaping influences -- Your child's development : Godward orientation -- You're in charge -- Examining your goals -- Reworking your goals -- Discarding unbiblical methods -- Embracing biblical methods : communication -- Embracing biblical methods : types of communication -- Embracing biblical methods : a life of communication -- Embracing biblical methods : the rod -- Embracing biblical methods : appeal to the conscience -- Shepherding the heart summarized -- Part 2 : Shepherding through the stages of childhood. Infancy to childhood : training objectives -- Infancy to childhood : training procedures -- Childhood : training objectives -- Childhood : training procedures -- Teenagers : training objectives -- Teenagers : training procedures.
"Revised and updated"--Cover.
"A Shepherding the heart resource"--Cover.
Includes index.
Keywords: Child rearing -- Religious aspects -- Christianity; Parenting -- Biblical teaching; Parent and child -- Biblical teaching; Rôle parental -- Enseignement biblique; Parents et enfants -- Enseignement biblique; Child rearing -- Religious aspects -- Christianity; Parent and child -- Biblical teaching; Parenting -- Biblical teaching; Nonfiction; Nonfiction